EFFECT OF BIOFERTILIZERS AND SPRAYING WITH MAGNESIUM AND CALCIUM ON THE YIELD AND ITS COMPONENTS OF SWEET CORN - WASAN. S. M. K.; Ayad.W. A. Al-juboori (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study was aimed to investigate response of two sweet corn hybrids to bacterial biofertilizers and spraying with Mg+2 and Ca+2 and their impact on the yield during fall season 2021 and spring season 2022, CASH seeds (H1) and ROI SOLEIL seeds (H2) were planted in pots, when they reached 2-3 leaves treated with four treatments which included without biofertilizer (B0), with Azospirillum brasilense (B1) with Pseudomonas fluorescens (B2) and the interaction with Azospirillum brasilense and Pseudomonas fluorescens (B3) then transferd to the field, and sprayed the seedling which included without spraying (N0), spraying with Mg++ and Ca++ with concentration of 25 mg L-1 (N1) and 50 mg L-1 each elements (N2), The experiment was carried out according to RCBD with in split plot arrangement. The results showed that the H1 hybrid had significant response in number of days to tasseling and silking of 50% of plants, the diameter of ear, number of rows.ear-1, The H2 hybrid had a significant response in the ear length for two seasons, B3 and N2 had significant impact to all the studied traits for two seasons. H1B3N2 had significant impact in number of days to tasseling and silking of 50% of plants, the ear diameter and number of rows.ear-1, H2B3N2 had significant impact to the length of the ear for the two seasons respectively